2016
DOI: 10.3389/fimmu.2016.00472
|View full text |Cite
|
Sign up to set email alerts
|

The Ly49E Receptor Inhibits the Immune Control of Acute Trypanosoma cruzi Infection

Abstract: The protozoan parasite Trypanosoma cruzi circulates in the blood upon infection and invades various cells. Parasites intensively multiply during the acute phase of infection and persist lifelong at low levels in tissues and blood during the chronic phase. Natural killer (NK) and NKT cells play an important role in the immune control of T. cruzi infection, mainly by releasing the cytokine IFN-γ that activates the microbicidal action of macrophages and other cells and shapes a protective type 1 immune response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Studies have shown that Ly49E is not involved in several pathophysiological situations, including malaria infection ( Filtjens et al, 2014 ), chemically induced colitis ( Van Acker et al, 2016 ), and different tumors ( Filtjens et al, 2016b ). However, young Ly49E-KO mice could control the parasite infection better ( Filtjens et al, 2016a ). Although Ly49E activation by uPA, a non-MHC class I ligand ( Van Den Broeck et al, 2008 ), could inhibit the effector functions of NK cell lines or fetal thymic NK cells, freshly isolated liver group 1 ILCs from Ly49E-deficient and WT mice did not differ in cytotoxic capacity in the presence of uPA ( Filtjens et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Ly49E is not involved in several pathophysiological situations, including malaria infection ( Filtjens et al, 2014 ), chemically induced colitis ( Van Acker et al, 2016 ), and different tumors ( Filtjens et al, 2016b ). However, young Ly49E-KO mice could control the parasite infection better ( Filtjens et al, 2016a ). Although Ly49E activation by uPA, a non-MHC class I ligand ( Van Den Broeck et al, 2008 ), could inhibit the effector functions of NK cell lines or fetal thymic NK cells, freshly isolated liver group 1 ILCs from Ly49E-deficient and WT mice did not differ in cytotoxic capacity in the presence of uPA ( Filtjens et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver trNK cells in mice are also functionally unique as they exhibit a higher level of baseline activation relative to splenic or liver cNK cells ( 56 ). They are larger and more granular, and express Ly49E, which mediates responses to liver-specific infections such as T. cruzi ( 173 ). Cytokine release is more efficient from these cells, TNFα, GM-CSF and IL-2 are all increased, and their high expression of TRAIL and FasL makes them better at inducing target cell apoptosis by alternative killing.…”
Section: Integrins As Markers For Residencymentioning
confidence: 99%
“…At 6–7 weeks post-injection, the mice were sacrificed by cervical dislocation and perfused with PBS. Single-cell suspensions of liver, spleen, bone marrow, and intestinal LPL were generated as previously described ( Van Acker et al, 2017 ; Filtjens et al, 2016 ; Filtjens et al, 2013 ). Lungs were cut in pieces and digested in RPMI1640 (Life Technologies) supplemented with 2% FCS, collagenase D (2 mg/mL, Roche), and Dnase I (0.2 mg/mL, Roche).…”
Section: Methodsmentioning
confidence: 99%